2011
DOI: 10.1039/c0ee00379d
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for modulating the morphology of supported metal nanoparticles in hydrodesulfurization catalysts

Abstract: This article proposes a novel cetyltrimethylammonium bromide-and fluorine-assisted hydrothermal deposition method for modulating the morphology of supported metal nanoparticles in NiWF/Al 2 O 3 hydrodesulfurization (HDS) catalysts. The proposed approach significantly promotes the dispersion of supported W species by bridging and anchoring the precursor of W species onto the surface of fluorinated Al 2 O 3 as well as restraining the subsequent aggregation of W species in calcination. The dual effects of the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 99 publications
(85 reference statements)
2
47
0
3
Order By: Relevance
“…In addition to the surface Ni species, the nature of promoter species (Cr, Mo and W) on the catalyst surface has also been investigated by XPS (Figure S3) . The surface composition obtained from XPS analysis revealed a relatively high ratio of Mo/Si as compared to Cr/Si and W/Si ratios (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the surface Ni species, the nature of promoter species (Cr, Mo and W) on the catalyst surface has also been investigated by XPS (Figure S3) . The surface composition obtained from XPS analysis revealed a relatively high ratio of Mo/Si as compared to Cr/Si and W/Si ratios (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 3B shows that no diffraction peak attributed to the bulk NiO phase is observed in the XRD patterns, possibly because of the high dispersion of NiO particles, whose size is <4 nm and thus beyond the detectability of XRD [42].…”
Section: Characterizations Of Catalystsmentioning
confidence: 90%
“…The textural parameters of the above samples are listed in Table 1. It can be seen that compared with c-Al 2 O 3 , the HNC-Al 2 O 3 composite has a decreased average pore diameter and pore volume, also indicating the successful deposition of W-based HNCs into the pore channels of c-Al 2 O 3 [42]. W-HHD, obtained by drying and calcining the HNC-Al 2 O 3 composite, has a larger pore volume and average pore diameter than its precursor, due to the decomposition of the organic shells of W-based HNCs during the calcination step.…”
Section: Characterizations Of W-based Hncsmentioning
confidence: 92%
See 1 more Smart Citation
“…Although noble metal catalysts had an eminent catalytic performance, the high cost and low abundance hampered their large‐scale application. Therefore, conventional hydrodesulfurization catalysts, such as sulfided Ni–W, Co–Mo, and Ni–Mo catalysts, were widely studied in the deoxygenation process . Verma et al reported a route to produce aviation fuel with a sulfided Ni–Mo catalyst on a ZSM‐5 support at 410 °C and 50 bars, where a 54% yield of jet‐fuel range alkanes was obtained.…”
Section: Introductionmentioning
confidence: 99%